Integrating forage technologies on smallholder farms in the upland tropics - Roothaert, Ralph L.; Horne, P.; Stür, Werner W. (2003)
In the past, adoption of forage technologies has been poor. This paper considers the reasons for this low level of adoption and how the situation has changed in recent years. Experiences, mostly in south-east Asia and some in east Africa, have shown that participatory approaches in the development of technology are the key to integration of forages into smallholder upland farming systems. This paper describes how projects went through the formal and informal stages of forage evaluation. Several key characteristics of communities were identified that determined whether forages could have an impact. A participatory approach was developed, which enhanced both forage technology development and its scaling-out to new areas. Some important data were generated on the environmental adaptation of forage varieties. A model for scaling-out forage technologies was developed. There are several stages of forage adoption, in which grass and legume species play different roles. Challenges for the future are to strengthen participatory approaches in the development of technology, especially in the process of scaling-out such developments.